2003
DOI: 10.1037/0021-843x.112.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The construct validity of depressive personality disorder.

Abstract: This study examined the construct validity of depressive personality disorder (DPD: American Psychiatric Association, 1994). Adult psychiatric outpatients (N = 900) underwent comprehensive Axis I and II evaluations and provided data on 4,768 of their 1st-degree relatives. Despite modest overlap, DPD was not redundant with any Axis I or II disorder. Participants with DPD exhibited more Axis I and Axis II comorbidity, and greater psychosocial dysfunction, than participants without DPD. Relatives of participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
82
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 38 publications
13
82
0
Order By: Relevance
“…The highest correlations (>.50) were seen with avoidant, dependent, and borderline PD. This finding is in line with several other studies (Huprich, 2004;Huprich et al, 2006;Klein & Shih,1998;Markowitz et al, 2005;McDermut et al, 2003), including one that used Pearson's correlations (Huprich, 2004). Huprich found that DPD correlated positively and significantly with all PDs except antisocial, histrionic, and obsessive-compulsive PD.…”
Section: Discussion Associations Between Dpd and The 10 Dsm-iv Pdssupporting
confidence: 81%
See 2 more Smart Citations
“…The highest correlations (>.50) were seen with avoidant, dependent, and borderline PD. This finding is in line with several other studies (Huprich, 2004;Huprich et al, 2006;Klein & Shih,1998;Markowitz et al, 2005;McDermut et al, 2003), including one that used Pearson's correlations (Huprich, 2004). Huprich found that DPD correlated positively and significantly with all PDs except antisocial, histrionic, and obsessive-compulsive PD.…”
Section: Discussion Associations Between Dpd and The 10 Dsm-iv Pdssupporting
confidence: 81%
“…Several studies addressing diagnostic overlap have been published, both with regard to mood disorders (Klein & Miller, 1993;Klein & Shih, 1998;McDermut, Zimmerman, & Chelminski, 2003;Ryder, Bagby, & Dion, 2001;Ryder, Bagby, & Schuller, 2002) and PDs (Huprich, 2004;Huprich, Zimmerman, & Chelminski, 2006;Klein & Shih, 1998; © 2012 The Guilford Press Address correspondence to Dr. Ragnhild E. Ørstavik, Norwegian Institute of Public Health, Box 4404, Nydalen N-0403, Oslo, Norway; ragnhild.orstavik@fhi.no. This article was accepted under the editorship of Paul S. Links.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there are no current conventions for determining rates of acceptable overlap, some have concluded that DPD fits within the broader conceptual space of the DD category (Bagby, Ryder, & Schuller, 2003), while others have determined DPD is a valid construct on its own (McDermut et al, 2003). The construct validity of DPD has now been extensively evaluated (see Huprich, 2009 for review), and there appears to be consensus that DPD and DD are, in fact, two separate clinical disorders.…”
mentioning
confidence: 99%
“…Large-scale studies examining rates of comorbidity between DPD and MDD or DD have generally shown about 50% overlap between disorders in clinical and nonclinical samples (Hirschfeld & Holzer, 1994;Markowitz et al, 2005;McDermut, Zimmerman, & Chelminski, 2003;Ørstavik, Kendler, Czajkowski, Tambs, & Reichborn-Kjennerud, 2007a). Because there are no current conventions for determining rates of acceptable overlap, some have concluded that DPD fits within the broader conceptual space of the DD category (Bagby, Ryder, & Schuller, 2003), while others have determined DPD is a valid construct on its own (McDermut et al, 2003).…”
mentioning
confidence: 99%